Common target genes of palatal and gingival fibroblasts for EMD: the microarray approach. (13th May 2014) - Gruber, R.; Stähli, A.; Miron, R. J.; Bosshardt, D. D.; Sculean, A.
<x xml:space="preserve">Abstract</x> Background and Objective Connective tissue grafts are frequently applied, together with Emdogain®, for root coverage. However, it is unknown whether fibroblasts from the gingiva and from the palate respond similarly to Emdogain. The aim of this study was therefore to evaluate the effect of Emdogain® on fibroblasts from palatal and gingival connective tissue using a genome‐wide microarray approach. Material and Methods Human palatal and gingival fibroblasts were exposed to Emdogain® and RNA was subjected to microarray analysis followed by gene ontology screening with Database for Annotation, Visualization and Integrated Discovery functional annotation clustering, Kyoto Encyclopedia of Genes and Genomes pathway analysis and the Search Tool for the Retrieval of Interacting Genes/Proteins functional protein association network. Microarray results were confirmed by quantitative RT‐PCR analysis. Results The transcription levels of 106 genes were up‐/down‐regulated by at least five‐fold in both gingival and palatal fibroblasts upon exposure to Emdogain®. Gene ontology screening assigned the respective genes into 118 biological processes, six cellular components, eight molecular functions and five pathways. Among the striking patterns observed were the changing expression of ligands targeting the transforming growth factor‐beta and gp130 receptor family as well as the transition of mesenchymal epithelial cells. Moreover, Emdogain® caused changes in expression of receptors for chemokines, lipids and hormones, and for transcription factors such as SMAD3, peroxisome proliferator‐activated receptor gamma and those of the ETS family. Conclusion The present data suggest that Emdogain® causes substantial alterations in gene expression, with similar patterns observed in palatal and gingival fibroblasts.